2022
DOI: 10.3389/fcimb.2022.1005730
|View full text |Cite
|
Sign up to set email alerts
|

The interactions between traditional Chinese medicine and gut microbiota: Global research status and trends

Abstract: BackgroundThere is a crosstalk between traditional Chinese medicine (TCM) and gut microbiota (GM), many articles have studied and discussed the relationship between the two. The purpose of this study is to use bibliometric analysis to explore the research status and development trends of the TCM/GM research, identify and analyze the highly cited papers relating to the TCM/GM.MethodsA literature search regarding TCM/GM publications from 2004 to 2021 was undertaken on August 13, 2022. The main information (full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 133 publications
1
2
0
Order By: Relevance
“…The earliest understanding of the mammary gland in Chinese medicine can be traced back to the Nei Jing, where it is written that “a woman’s breast belongs to the liver, while the nipple belongs to the stomach” and that “Chong and Ren meridians can regulate the Qi and blood of the 12 meridians and they stop at the breast upward and form menstruation downward”, which explains the close relationship between the breast and the spleen and stomach in terms of physiological function and meridian affiliation. Chinese herbal medicine has a very beneficial effect on the balance of the intestinal micro-ecolozy, and the intestinal microbiota coincides with the theory of “spleen and stomach” in Chinese Medicine ( 21 23 ). Atractylodes Macrocephala Rhizoma is the dry rhizome of the Asteraceae plant Atractylodes macrocephala Koidz , which has the effect of strengthening the spleen and stomach, drying and dampening water.…”
Section: Introductionsupporting
confidence: 66%
“…The earliest understanding of the mammary gland in Chinese medicine can be traced back to the Nei Jing, where it is written that “a woman’s breast belongs to the liver, while the nipple belongs to the stomach” and that “Chong and Ren meridians can regulate the Qi and blood of the 12 meridians and they stop at the breast upward and form menstruation downward”, which explains the close relationship between the breast and the spleen and stomach in terms of physiological function and meridian affiliation. Chinese herbal medicine has a very beneficial effect on the balance of the intestinal micro-ecolozy, and the intestinal microbiota coincides with the theory of “spleen and stomach” in Chinese Medicine ( 21 23 ). Atractylodes Macrocephala Rhizoma is the dry rhizome of the Asteraceae plant Atractylodes macrocephala Koidz , which has the effect of strengthening the spleen and stomach, drying and dampening water.…”
Section: Introductionsupporting
confidence: 66%
“…As far as we know, no bibliometric studies have been reported to assess the hotspots and research trends of TCM intervention in IM for obesity prevention and treatment. Therefore, this research leverages acclaimed bibliometric software like VOSviewer and CiteSpace for analysis (Yang et al, 2022;Zhang et al, 2022;Wei et al, 2023). In the course of our investigation, we observed a consistent increase in the quantity of studies pertaining to TCM intervention in IM for obesity prevention and treatment since 2009.…”
Section: Introductionmentioning
confidence: 57%
“…The biological applications of MXene have been discussed in numerous review publications, however, these mainly focus on the current status of overall biological applications ( Huang et al, 2018 ; Koyappayil et al, 2022 ; Parajuli et al, 2022 ) or only address a specific biomedical application such as their use as antibacterial agents, biosensors or for cancer imaging and treatment ( Ali et al, 2022 ; Hao et al, 2022 ; Ranjbari et al, 2022 ). Bibliometric analysis is a research method that statistically evaluates and visually presents the current state-of-the-art, most influential studies and upcoming trends of a given field of research ( Yang et al, 2022 ). Through quantitative and qualitative analysis of different metrics such as countries, institutional authors, keywords, etc.…”
Section: Introductionmentioning
confidence: 99%